دراسة تحليلية لأعداد المرضى المراجعين في مشفى الباسل لأمراض القلب في محافظة اللاذقية (Latakia University Journal - Economic and Legal Sciences Series, 2018)
إنَّ القطاع الصحي وخاصةً المشافي ومنها التخصصية على تماس مباشر وحيوي ودائم لحاجات المواطن الطالب للاستشفاء، فصحة الانسان هي إحدى المطالب الأساسية لاستمرار حياته وقدرته على الإنتاج والعمل. ولمعرفة الدور الذي يقوم به مشفى الباسل لأمراض وجراحة القلب من خلال استقباله ومعالجته للمرضى تمت دراسة تطور أعداد المراجعين في مشفى الباسل لأمراض القلب في محافظة اللاذقية خلال الفترة من 2014 حتى 2017. وذلك للوقوف على الواقع الحقيقي للمشفى ومدلولات الأرقام المتزايدة للمراجعين بسبب الأمراض القلبية على اختلاف التشخيص والعلاج. وبعد الدراسة والتحليل توصل البحث للنتائج التالية: 1-  يتوزع المرضى من الجنسين ضمن الفئات العمرية المختلفة، وتميل للارتفاع عند الذكور بالنسبة للإناث. 2-  تتطور أعداد المرضى المقبولين في مشفى الباسل من الذكور والإناث بشكلٍ متزايد بالنسبة للزمن. 3-  وجود علاقة ارتباطية بين أعداد المراجعين بالنسبة للنوع الاجتماعي. The health sector, especially the hospitals, including specialization on the direct contact and vital and permanent needs of the citizen student for hospitalization, human health is one of the basic demands for the continuation of his life and ability to produce and work. To study the role played by Al-Basel Hospital for Cardiology and Cardiology by receiving and treating patients, a study was conducted on the development of the number of patients at Al-Basel Hospital for Cardiology in Lattakia Governorate from 2014 to 2017. To find out the true reality of the hospital and the implications of the increasing numbers of patients due to heart disease Diagnosis and treatment. After study and analysis, the research results in the following results: 1 - The distribution of patients of both sexes within different age groups, and tend to rise in males for females. 2. The number of patients admitted to Al-Basil Hospital is increasing for both males and females. 3 - There is a correlation between the number of reviewers for gender.